Effects of Topical Anesthetics on Behavior, Plasma Corticosterone, and Blood Glucose Levels after Tail Biopsy of C57BL/6NHSD Mice (Mus musculus) - Dudley, Emily S (J Am Assoc Lab Anim Sci, 2016)
Tail biopsy is a common procedure that is performed to obtain genetic material for determining genotype of transgenic mice. The use of anesthetics or analgesics is recommended, although identifying safe and effective drugs for this purpose has been challenging. We evaluated the effects of topical 2.5% lidocaine–2.5% prilocaine cream applied to the distal tail tip at 5 or 60 min before biopsy, immersion of the tail tip for 10 seconds in ice-cold 70% ethanol just prior to biopsy, and immersion of the tail tip in 0.5% bupivacaine for 30 s after biopsy. Mice were 7, 11, or 15 d old at the time of tail biopsy. Acute behavioral responses, plasma corticosterone, and blood glucose were measured after biopsy, and body weight and performance in elevated plus maze and open-field tests after weaning. Ice-cold ethanol prior to biopsy prevented acute behavioral responses to biopsy, and both ice-cold ethanol and bupivacaine prevented elevations in corticosterone and blood glucose after biopsy. Tail biopsy with or without anesthesia did not affect body weight or performance on elevated plus maze or open-field tests. We recommend the use of ice-cold ethanol for topical anesthesia prior to tail biopsy in mice 7 to 15 d old.